HIV and lymphocyte dynamics - Ho, David D (Vaccine, 2002)
To understand the dynamics of HIV replication in vivo, we used potent antiviral drugs to perturb the equilibrium between the virus and the infected host. Careful analyses of the viral decay following effective treatment have revealed that viral particles are cleared with a half life of similar to 30 min and that productively infected CD4 T-cells turn over with a half life of similar to 1 day. These kinetic measurements in turn formed the foundation for combination antiretroviral therapy that has successfully controlled HIV replication in many patients. However, HIV has not been eradicated from any patient because (1) the virus can lay dormant and persist within long-lived resting memory CD4 T-cells and (2) viral replication has not been completely inhibited even when the virus is undetectable in blood. We recently examined whether a new four-drug regimen (lopinavir/ritonavir, efavirenz, tenofovir, and lamivudine) might be more potent than commonly used combinations by comparing the initial decay rate of plasma viremia after starting therapy. Frequent measurements showed that viral loads decreased more sharply than previously observed, with the average slope of first-phase decay being - 1.0 per day. This finding has two major implications. First, the half life of a productively infected CD4 lymphocyte is even shorter ( less than or equal to 0.7 day) than previously believed. Second, antiretroviral regimens currently in use are significantly less potent ( similar to 80% relative potency) than what can be achieved with the new drug combination. The dynamics of T-cells during HIV infection have remained unresolved because of conflicting research findings. Using deuterated glucose to label the DNA of proliferating cells in vivo, we studied T-cell dynamics in normal subjects and HIV-1-infected patients naive to antiretroviral drugs. The results were analyzed using a newly developed mathematical model to determine fractional rates of lymphocyte proliferation and death. In CD4+ T-cells, mean proliferation and death rates were elevated by 6.3- and 2.9-fold, respectively, in infected patients compared with normal controls. In CD8+ T-cells, the mean proliferation rate was 7.7-fold higher in HIV-1 infection, but the mean death rate was not significantly increased. Some of the infected patients underwent subsequent deuterated glucose labeling studies after initiating antiretroviral therapy. The lymphocyte proliferation and death rates in both CD4+ and CD8+ cell populations were substantially reduced by 5-11 weeks and nearly normal by 1 year. Taken together, these new findings strongly indicate that CD4+ lymphocyte depletion seen in AIDS is primarily a consequence of increased cellular destruction, not decreased cellular regeneration.